Controverses autour de la question identitaire des lettres belges (1881—1980) - Komandera, Aleksandra (Romanica Silesiana)
The aim of this paper is to discuss some questions concerning French-Belgian literature between 1881 and 1980. Since 1830, when Belgium became an independent country, controversies about autonomy and dependence of its national writing have involved many authors or theorists, and divided its literary scene. The magazine La Jeune Belgique argued with the old generation of writers and fought against the idea of social art and symbolists’ innovations and exaggerations in literature. Then, some regionalist authors rejected French domination by focusing on local scenery and characters. They were criticized soon by writers forming a group called groupe du Lundi, who claimed the affiliation to French literature. This view was challenged in the 70s and 80s, first, by the notion of belgitude, then, in La Belgique malgré tout. Key words: Controversy, Belgian literature in French, identity, autonomy, dependence.